Examining the sentence superiority effect for sentences presented and reported in forwards or backwards order. (March 2020) - Roverud, Elin; Bradlow, Ann R.; Kidd, Gerald
Abstract: Memory for speech benefits from linguistic structure. Recall is better for sentences than for random strings of words (the "sentence superiority effect"; SSE), and evidence suggests that ongoing speech may be organized advantageously as clauses in memory (recall by word position shows within-clause U shape). In this study, we examined the SSE and clause-based organization for closed-set speech materials with low semantic predictability and without typical prosody. An overall SSE was observed and accuracy by word position was enhanced at the clause boundaries for these materials. Next, we tested the effects of mental manipulation on the SSE and clause-based organization. Listeners heard word strings that were syntactic, were arranged syntactically then presented backwards, or were random draws. Participants responded to materials as presented or in reversed order, requiring mental manipulation. Clause-level organization was apparent only for materials presented in syntactic order regardless of response order. After accounting for benefits due to reductions in uncertainty for these close-set materials, an SSE was present for syntactic materials regardless of response order, and for the syntactic backwards condition with reverse-order response (yielding a syntactically correct sentence in the response). Thus, the SSE was both resistant to and could be obtained following mental manipulation.